Piano Sonata no. 21 in C major, op. 53 (Simrock) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Waldstein, Ferdinand Ernst, Graf von, 1762-1823 (dedicatee):::Contributor:::::::::::: (Bonn; N. Simrock; Germany)
Piano sonata no. 21 in C Major, op. 53, later issue of the Simrock edition with lithographed t.p. decorated in blue tint and illustrated with three putti between two pillars.